Vibration Analysis and Control: A Cantilever Beam with a Tuned Mass Absorber Under Harmonic Loading and Mass at the Free End - Dhakal, Pusparaj; Chhantyal, Bikki; Chandra Luintel, Mahesh (KEC Journal of Science and Engineering, 2026)
Vibration of a cantilever beam subjected to harmonic loading with a tip mass is mitigated by employing a tuned mass absorber at the free end. The beam is modeled using the Euler-Bernoulli theory to establish equations of motion for both the beam and the absorber. Stiffness and mass values ensuring zero deflection at the free end are determined via Galerkin’s Method with a polynomial trial function. The analytical results are validated through FEM simulations in ANSYS Mechanical. The close agreement between computational and analytical outcomes establishes a foundation for advanced computational investigations.